Cost Reduction and Increase of Reliability for Remote PV-Systems by Satellite - Krauter, Stefan; Depping, T. (Proceedings of the 19th European Photovoltaic Solar Energy Conference and Exhibition, Paris (Frankreich), 7.–11. Juni 2004, S. 3527–3530)

PV in Combination with Micro Wind Turbines for Rural Household Electrification in the Northeast of Brazil - Krauter, Stefan; Calvacante, F. S. A.; Cunha, M. S.; de Lima, L. C. (Proceedings of the 19th European Photovoltaic Solar Energy Conference and Exhibition, Paris (Frankreich), 7.–11. Juni 2004, S. 3532)

Renewable Energy in Latin America - Krauter, Stefan; Kissel, J. (Renewable Energy World)

Activities concerning the Set-up of an International University for Renewable Energy - Krauter, Stefan (Proceedings of the International Seminar on Hydrogen Technologies, Buenos Aires (Argentina), 7.–9. September 2004)

Security Aspects of Internet Voting - Schryen, Guido (37th Annual Hawaii International Conference on System Sciences)
Voting via the Internet has become a feasible option for political as well as non-political ballots. However, there are many obstacles which have to be overcome, especially legal restrictions have to be transformed into technical and security solutions. The article starts with a brief presentation of advantages and disadvantages of Internet ballots and presents application fields and pilot schemes. Then, technological security aspects are derived due to democratic basic principles. Especially the applied voting procedures are critical in security terms. Hence, the most relevant cryptographic protocols are presented and their drawbacks and shortcomings are identified. However, this article does not propose a new voting protocol. Beyond fixing cryptographic procedures for ballots, more elements are to be specified, e.g. responsibilities and rights of involved authorities or security precautions regarding hardware and software. For this reason, a structural security framework for electronic voting systems is presented which can be used for their composition and analysis.

Internationalisierung mittelständischer Unternehmen: Fünf Thesen zum Auslandsmarkterfolg - Kabst, Rüdiger

International komparatives Personalmanagement: Evidenz, Methodik & Klassiker des "Cranfield Projects on International Human Resource Management" - Kabst, Rüdiger; Brewster, C (Handwörterbuch des Personalwesens)

The Netherlands and Germany: Flexibility or Rigidity - Dietz, B; Hoogendoorn, J; Kabst, Rüdiger; Schmelter, A (Human Resource Management in Europe: Evidence of Convergence?)

Transaktionskostentheorie: Einführung, kritische Diskussion und Ansätze zur Weiterentwicklung - Kabst, Rüdiger (Personaltheorie als Beitrag zur Theorie der Unternehmung)

Theoretical Perspectives for Human Resource Management: The German Discussion - Kabst, Rüdiger; Weber, W (Management Revue: The International Review of Management Studies.)

SIMULTANEOUSLY MODELING CONDITIONAL HETEROSKEDASTICITY AND SCALE CHANGE - Feng, Yuanhua (Econometric Theory)

Non- and Semiparametric Regression with Fractional Time Series Errors - Feng, Yuanhua

A robust data-driven version of the Berlin Method - Heiler, Siegfried; Feng, Yuanhua (Zeitreihenanalyse in der empirischen Wirtschaftsforschung)

Wettbewerbsfähigkeit und Dynamik institutioneller Standortbedingungen: Ein empirischer Test des „Varieties-of-Capitalism “-Ansatzes - Paunescu, Mihai; Schneider, Martin (Schmollers Jahrbuch: Journal of Applied Social Science Studies/Zeitschrift für Wirtschafts-und Sozialwissenschaften)

Occupational job creation: patterns and implications - Fahr, Rene; Sunde, Uwe (Oxford Economic Papers)

A Comparative Analysis of Job Entry Methods in Japan, the US and Europe (Japanese) - Toshihiro, KODAMA; Yoshio, HIGUCHI; Masahiro, ABE; Fahr, Rene

Loafing or Learning? - Fahr, Rene (The Economics of Time Use)

Wettbewerbsfähigkeit und Dynamik institutioneller Standortbedingungen: Ein empirischer Test des „Varieties-of-Capitalism “-Ansatzes - Paunescu, Mihai; Schneider, Martin (Schmollers Jahrbuch: Journal of Applied Social Science Studies/Zeitschrift für Wirtschafts-und Sozialwissenschaften)

Wertorientiertes Beziehungsmarketing in Kunden-Lieferantenbeziehungen. - Eggert, A

The Evolution of Relationship Marketing and the International Colloquia - Bliemel, Friedhelm; Eggert, Andreas; Fassott, Georg; Ballantyne, David (Journal of Relationship Marketing)

Dynamic Meta Modeling with Time: Specifying the Semantics of Multimedia Sequence Diagrams - Hendrik Hausmann, Jan; Heckel, Reiko; Sauer, Stefan (Software and Systems Modeling)
UML offers different diagram types to model behavior and dynamics of software systems. In some domains like embedded real-time systems or multimedia systems, it is necessary to include specifications of time since the correctness of these applications depends on the fulfillment of temporal requirements in addition to functional requirements. UML thus already incorporates language features to model time and temporal constraints. Such model elements must have an equivalent in the semantic domain. We have proposed Dynamic Meta Modeling (DMM) as a means for the specification of the formal operational semantics of UML models by applying graph transformation to the meta modeling of dynamic behavior. Within this paper, we extend this approach to also account for time by building on timed graph transformations. We apply these concepts to the domain of multimedia application modeling in which we adopt UML sequence diagrams. The DMM rules with time then specify an interpreter that can be used to analyze or test a model of multimedia sequence diagrams.

Adaptive Cruise Controller Case Study - Krupp, Alexander; Lundkvist, Ola; Schattkowsky, Tim; Snook, Colin (UML-B System Specification for Proven Electronic Design)
We present the adaptive cruise controller case study for B modelling and the model checking by RAVEN. Individual translations of B operations, data types, and invariants to the RAVEN Input Language are presented by the example of the case study.

Workflow Management Middleware for Secure Distance-Spanning Collaborative Engineering - Schattkowsky, Tim; Mueller, Wolfgang; Pawlak, Adam (Workflow Handbook 2004)
This article presents the E-COLLEG Tool Registration and Management Services (TRMS) with open XML-based data exchange, tool integration and remote invocation capabilities. TRMS is a workflow management middleware tailored to distance spanning engineering collaboration and security enabled data exchange. The infrastructure is validated through two industrial Intranet-crossing case studies between Polish, French, and German chip manufacturing industries applying real-world development scenarios. In both application scenarios, common engineering practices have been identified and built into engineering workflows. Further, the current truly pan-European collaborative industrial scenarios show promising results with respect to the stability of the implemented software and easy application and flexibility of the provided interfaces.

Consistency Management of Object-Oriented Behavioral Models - Küster, Jochen

Visuelle Modellierung agentenbasierter Systeme - Depke, Ralph
This dissertation describes an approach to the visual modeling of software systems which are composed of autonomous and proactive software entities interacting with their environment. These entities are named software agents. More and more software systems are distributed, dynamic and open with respect to their environment. Software agents shall ease the development of such systems. Agent based systems provide a modular structure. They are robust and can be adapted dynamically to changing requirements. The notion of software agent relies on the fundamental properties of autonomy, proactivity and structured interaction. According to these properties agents are distinguished from objects and components. For the development of agent based systems an appropriate modeling language and a process model describing the correct usage of the language are demanded. For both aspects only unsufficient or incomplete approaches exist. This thesis contributes to the solution in the following way: A new abstract and formal model of agent based systems shows, that the fundamental properties can be expressed precisely. Differently from existing models not only a single agent but a multi agent system can be modeled. The most important architectural models of agent-based systems are compatible with the abstract model. The rather restricted structure of the abstract model motivates the refinement by a model of coupled I/Oautomata. The Unified Modeling Language is widely used in industrial software development. Therefore, the new language AML (Agent Modeling Language) for the development of agent-based systems is defined as a UML profile. The semantics of AML models is defined in the semantic domain of graph transformation. The semantic domain is restricted to an adequate agent-oriented domain. There the constituents of the fundamental agent properties are defined. Agent based systems which are described using AML are shown to be compatible with I/O-automata model of multi agent systems. Constituents for proactivity are goals and strategies. In this thesis, it is shown that the reachability of goals through the application of strategies can be checked by applying a model checking method. The new process model APM describes, how the language AML can be applied to the modeling of agent-based systems.

Free-standing, optically pumped, GaN∕InGaN microdisk lasers fabricated by photoelectrochemical etching - Haberer, E. D.; Sharma, R.; Meier, Cedrik; Stonas, A. R.; Nakamura, S.; DenBaars, S. P.; Hu, E. L. (Applied Physics Letters)

Synthesis of High Purity Silicon Nanoparticles in a Low Pressure Microwave Reactor - Knipping, Jörg; Wiggers, Hartmut; Rellinghaus, Bernd; Roth, Paul; Konjhodzic, Denan; Meier, Cedrik (Journal of Nanoscience and Nanotechnology)

Wave function mapping of self-assembled quantum dots by capacitance spectroscopy - Wibbelhoff, O; Meier, Cedrik; Lorke, A; Schafmeister, P; Wieck, A.D (Physica E: Low-dimensional Systems and Nanostructures)

Understanding Model Transformation by Classification and Formalization - Sendall, Shane; Hauser, Rainer; Koehler, Jana; Küster, Jochen; Wahler, Michael (Proceedings of the Workshop on Software Transformation Systems (STS 2004, satellite event of the 3rd International Conference on Generative Programming and Component Engineering (GPCE 2004)), Vancouver (Canada))

Behavior-Preserving Refinement Relations between Dynamic Software Architectures - Heckel, Reiko; Thöne, Sebastian (Proceedings of the workshop on Algebraic Development Techniques (WADT 2004), Barcelona (Spain))

A Formal Approach to Service Specification and Matching based on Graph Transformation - Heckel, Reiko; Cherchago, Alexey; Lohmann, Marc (Proceedings of the First International Workshop on Web Services and Formal Methods (WSFM 2004), Pisa, Italy)

Systematic Validation of Model Transformations - Küster, Jochen (Proceedings 3rd UML Workshop in Software Model Engineering (WiSME 2004), Lisbon (Portugal))

Comparing two Model Transformation Approaches - Küster, Jochen; Sendall, Shane; Wahler, Michael (Proceedings of the Workshop on OCL and Model Driven Engineering (satellite event of the UML 2004), Lisbon (Portugal))

Towards Inconsistency Handling of Object-Oriented Behavioral Models - Küster, Jochen (International Workshop on Graph Transformation (GT-VMT 2004), Barcelona (Spain))

UML for FPGA Synthesis - Schattkowsky, Tim; Rettberg, Achim (Proceedings of the International Workshop on UML for SoC Design (UML-SOC 2004), San Diego, CA (USA))

Taming Model Round-Trip Engineering - Sendall, Shane; Küster, Jochen (Proceedings of Workshop on Best Practices for Model-Driven Software Development (satellite event of the 19th Annual ACM Conference on Object-Oriented Programming, Systems, Languages, and Applications (OOPSLA 2004)), Vancouver (Canada))

Virtual conference: a telecooperative learning environment - Kremer, H.-Hugo (Networked Learning 2004. A research based conference on e-learning in higher education and lifelong learning)

Organisation und didaktische Ausrichtung des "Praxissemesters" im Rahmen des Diplomstudiengangs Wirtschaftspädagogik an der Universität Konstanz - Deißinger, T.; Kremer, H.-Hugo (Theorie-Praxis-Verzahnung in der beruflichen und gymnsasialen Lehrerbildung. Das Praxissemester in Baden-Württemberg.)

Qualifizierungsnetzwerke - Lernumgebung für Lehrkräfte? - Kremer, H.-Hugo (Lernfelder gestalten - miteinander Lernen - Innovationen vernetzen. Ergebnisse der 1. CULIK Fachtagung (12.05.2004))

Virtual conference - a cooperative learning environment for teacher education? - Kremer, H.-Hugo (The annual conference of the Association for Information Technology in Teacher Education)

Qualifizierungsnetzwerke - Lernumgebung für Lehrkräfte - Kremer, H.-Hugo (Lernfelder gestalten - miteinander Lernen - Innovationen vernetzen. Ergebnisse der 1. CULIK Fachtagung)

Cross-layer optimization of OFDM transmission systems for MPEG-4 video streaming - Gross, James; Klaue, Jirka; Karl, Holger; Wolisz, Adam (Computer Communications)

Ambient networks: An architecture for communication networks beyond 3G - Niebert, Norbert; Schieder, Andreas; Abramowicz, Henrik; Malmgren, G.; Sachs, Joachim; Horn, Uwe; Prehofer, Christian; Karl, Holger (IEEE Wireless Communications)

Improving the Energy Efficiency of Directed Diffusion Using Passive Clustering - Handziski, Vlado; Köpke, Andreas; Karl, Holger; Frank, Christian; Drytkiewicz, Witold (Wireless Sensor Networks, First European Workshop, EWSN 2004, Berlin, Germany, January 19-21, 2004, Proceedings)

Research Challenges in Mobility and Moving Networks: An Ambient Networks View - Typpö, Ville; Eisl, Jochen; Höller, Jan; Agüero, Ramon; Karl, Holger (Broadband Satellite Comunication Systems and the Challenges of Mobility - IFIP TC6 Workshops on Broadband Satellite Communication Systems and Challenges of Mobility, World Computer Congress, August 22-27, 2004, Toulouse, France)

Consistency challenges of service discovery in mobile ad hoc networks - Frank, Christian; Karl, Holger (Proceedings of the 7th International Symposium on Modeling Analysis and Simulation of Wireless and Mobile Systems, MSWiM 2004, Venice, Italy, October 4-6, 2004)

A Geometric Derivation of the Probability of Finding a Relay in Multi-rate Networks - Marie Feeney, Laura; Hollos, Daniel; Kubisch, Martin; Mengesha, Seble; Karl, Holger (NETWORKING 2004, Networking Technologies, Services, and Protocols; Performance of Computer and Communication Networks; Mobile and Wireless Communication, Third International IFIP-TC6 Networking Conference, Athens, Greece, May 9-14, 2004, Proceedings)

Regionalizing global optimization algorithms to improve the operation of large ad hoc networks - Hollos, Daniel; Karl, Holger; Wolisz, Adam (2004 IEEE Wireless Communications and Networking Conference, WCNC 2004, Atlanta, Georgia, USA, 21-25 March 2004)

Queue-driven cut-through medium access in wireless ad hoc networks - Raguin, David; Kubisch, Martin; Karl, Holger; Wolisz, Adam (2004 IEEE Wireless Communications and Networking Conference , WCNC 2004, Atlanta, Georgia, USA, 21-25 March 2004)

Data Transmission in Mobile Communication Systems - Karl, Holger (Location-Based Services)